2021
DOI: 10.1007/s00784-021-04034-z
|View full text |Cite
|
Sign up to set email alerts
|

Oral health-related quality of life in patients with early rheumatoid arthritis is associated with periodontal inflammation and painful temporomandibular disorders: a cross-sectional study

Abstract: Objectives To evaluate oral health-related quality of life (OHRQoL) in early rheumatoid arthritis (ERA) patients and individuals at risk of rheumatoid arthritis (RA) compared to healthy controls, and to explore possible associated factors. Materials and methods Fifty ERA patients, 50 at-risk individuals, and 50 age and gender matched healthy controls were recruited. OHRQoL (Oral Health Impact Profile-14 (OHIP-14)); number of decayed, missing, and filled te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
(54 reference statements)
2
4
0
Order By: Relevance
“…In line with age, gender exhibited a positive but weak prediction with OHIP-14 scores, yet this effect was not statistically significant (p > 0.05). This suggests that, in this study, gender differences did not significantly predict oral health impact, aligning with the findings of Branco et al and Kroese et al [7,15].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with age, gender exhibited a positive but weak prediction with OHIP-14 scores, yet this effect was not statistically significant (p > 0.05). This suggests that, in this study, gender differences did not significantly predict oral health impact, aligning with the findings of Branco et al and Kroese et al [7,15].…”
Section: Discussionsupporting
confidence: 92%
“…The interquartile range of the OHIP-14 scores suggests that some patients and controls may experience varying degrees of impact on oral health within each group. Similar outcomes have been reported in various published studies [7,14,15].…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have shown that PISA is associated with several systemic diseases including CVD [ 27 ], dementia [ 28 ], rheumatoid arthritis [ 29 ] kidney disease [ 30 ], diabetes [ 31 ]. PISA has also been found to be associated with plasma CRP [ 30 , 32 ], a measure of systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, even though the OHIP-NL14 is associated with numerous oral health indicators, this study did not include a physical assessment of the dental status by an oral health care professional and oral health was self-reported. However, it has been reported that oral health assessed by dental health care professionals often agrees with self-reported oral health [26,41]. Considering the OHIP-NL14 as a measurement for oral health allows for a shift from traditional medical/dental criteria, such as teeth count or oral pain, to an oral health assessment that focuses on a person's social and emotional experience and physical functioning.…”
Section: Strengths and Limitationsmentioning
confidence: 99%